Mobile Augmented Reality Jurusan Sistem Komputer Universitas Diponegoro Berbasis Android (MARSISKOM) - Teguh Martono, Kurniawan; Kridalukmana, Rinta (Jurnal Sistem Komputer, 2014)
Department of Computer system Diponegoro University , Faculty of Engineering is one of the majors are still young . The department has several areas of specialization for students . Areas of specialization include Software Engineering , Computer Networks , Embedded Systems and Robotics and Multimedia . Majors but it also has some buildings that are used as a laboratory , classroom and centralized administration . To help facilitate students and the general public in recognizing or knowing the location of each of the buildings with the development of computer technology can be facilitated . One technology that can be applied is by using augmented reality technology which is combined with mobile communication devices . This study uses peracangan software system using the waterfall model . This model is a systematic approach and sequence ranging from system level requirements and then headed to the stage of analysis , design , coding , testing / verification , and maintenance . Referred to as step -by-step waterfall that must be passed pending the completion of the previous stage and run sequentially . System testing performed by menggukan black box testing which aims to determine the functionality of the system . System testing that has been done is stated that the system is run in accordance with what is expected . Testing the functionality of the system can be run on mobile devices with android operating system version of the jelly bean .